Autophagy participates in the unfolded protein response in Toxoplasma gondii. Issue 15 (20th July 2017) - Nguyen, Hoa Mai; Berry, Laurence; Sullivan, William J.; Besteiro, Sébastien
Abstract: Environmental and genetic perturbations of endoplasmic reticulum (ER) function can lead to the accumulation of unfolded proteins. In these conditions, eukaryotic cells can activate a complex signaling network called the unfolded protein response (UPR) to reduce ER stress and restore cellular homeostasis. Autophagy, a degradation and recycling process, is part of this response. The parasitic protist Toxoplasma gondii is known to be able to activate the UPR upon ER stress, and we now show that this pathway leads to autophagy activation, supporting the idea of a regulated function for canonical autophagy as part of an integrated stress response in the parasites. Abstract : In Toxoplasma, ER stress and starvation are potent activators of the eIF2α pathway that, in turn, regulates autophagy.